ECONOMIC EVALUATION AND RISK MANAGEMENT STRATEGY FOR COAL INFRASTRUCTURE PROJECT: A CASE STUDY OF PT. XYZ - Putri Devani, Fadhilah
This study analyzes the economic feasibility of the coal transportation and new port development project at PT. XYZ, South Sumatra. With a projected increase in coal production up to 15 million tons per year, this study evaluates four scenarios: maintaining the existing railway line and three alternatives for new infrastructure development using the Discounted Cash Flow (DCF), Monte Carlo Simulation, and Real Option Valuation (ROV) methods. The DCF analysis results show that Scenario 3 has the highest NPV of IDR 1.69 trillion, making it the most profitable option. Monte Carlo Simulation reveals the highest project success probability in Scenario 3, at 60.82%. Evaluation using the ROV approach, including Binomial Lattice, Black-Scholes, and Rainbow Option, confirms that Scenario 3 offers the highest option value and managerial flexibility, indicating the greatest potential profit amid market volatility. Therefore, this study recommends Scenario 3 as the most economically viable and optimal option for PT. XYZ to support increased coal production.